Even then - Wurster, Michael, 1940- (University of Pittsburgh Press, 2019)
A new collection of poetry from a founding member of the Pittsburgh Poetry Exchange.
Poems.
Keywords: American poetry -- 21st century.; POETRY -- General.; American poetry; 2000-2099; Poetry; poetry.; Poetry.; Poésie.